Comparative analysis of variability in the mid-latitude stratosphere and ionosphere in winter periods - Vesnin A. M. (Solar-Terrestrial Physics, 2022)
In this work, we perform a joint analysis of the spatial-temporal dynamics of ionospheric and stratospheric variability (with scales characteristic of internal gravity waves) at different longitudes of midlatitudes of the Northern Hemisphere. We analyze the winter periods of 2012–2013 and 2018–2019 when strong midwinter sudden stratospheric warmings (SSWs) occurred. An increase in the variability in the stratosphere is shown to occur in a limited latitude interval 40°–60° N in the region of existence of a winter circumpolar vortex. Under SSW conditions, the generation of wave disturbances in the stratosphere ceases manifesting itself in a significant decrease in the stratospheric variability index. Similar behavior is noted in the spatial-temporal dynamics of the index of the total electron content variability. The level of ionospheric variability at midlatitudes decreases significantly after SSW peaks. The decrease in the ionospheric variability can be explained by a reduction in wave generation in the stratosphere, associated with the destruction of the circumpolar vortex during SSWs.